Co-creating for Change: Ireland’s National Recognition of Prior Learning (RPL) in Higher Education Project (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2023)
While Ireland has demonstrated innovative Recognition of Prior Learning (RPL) practice, with deep-seated commitment to excellent practice, it is noteworthy that a series of challenges have prevented RPL from becoming a mainstream higher-education activity nationally. Several needs have been identified, which include: a shared understanding in relation to RPL; greater coherence and consistency of policy and practice within, and across, higher education institutions; and resourcing to enable providers to enhance their institutional commitment to RPL and to grow learner numbers (Murphy, 2019). The National RPL in Higher Education Project – with fourteen publicly funded higher education institutions as partners and funding from the Irish government – has a unique opportunity to meet these needs.This article will outline steps taken and learnings gleaned to date during Ireland’s National RPL in Higher Education Project. The project’s deliverables will be viewed through the lens of change-management and design-thinking literature, which have informed the evolution of this collaborative work to date. As this paper will illustrate, the project’s actions are shaped by design thinking: a ‘human-centred approach to innovation that puts […] human needs right at the forefront of the innovation process’ (Gruber et al., 2015). Key components of this project include creating a sense of urgency, forming powerful ‘guiding coalitions’, developing a vision, and systematic planning for short- and long-term ‘wins’ (Kotter, 1995). Co-creation is a vital element of design thinking (Vaugh & Ryan, 2015); it will be shown that this has been an essential factor in contributing to the project’s success to date.